Public policy and sustainability: How green core competence, government trust, and policy satisfaction influence green R&D investments in the private sector - Fadi Abdelfattah; Mohammed Salah; Khalid Dahleez; Riyad Darwazeh; Hussam Al Halbusi (Sustainable Futures)
This study examines how green innovation practices influence organizational capabilities and investments in sustainability within Omani firms. Grounded in Dynamic Capabilities Theory and Institutional Theory, it explores the relationship between Green Product Innovation Performance (GPIP), Green Process Innovation Performance (GPcIP), Green Core Competence (GCC), and Green Research and Development (R&D) Investments. Data collected from 214 top management personnel across diverse industries in Oman were examined via Structural Equation Modeling. The findings reveal that GPIP positively affects GCC, indicating that firms excelling in green product innovation enhance their strategic environmental capabilities. Conversely, GPcIP does not significantly impact GCC, suggesting that process innovations may need integration with broader strategies to influence core competencies effectively. GCC positively influences Green R&D Investments, showing that firms with solid environmental capabilities are more likely to finance sustainable innovation. Moreover, Trust in Government (TG) and Satisfaction with Sustainability Government Policies (SWGM) significantly moderate the relationships between GPIP, GPcIP, GCC, and Green R&D Investments. High levels of trust and satisfaction amplify these positive effects, highlighting the crucial role of a supportive institutional environment in fostering sustainable innovation. The study contributes to theoretical frameworks by integrating internal capabilities with external institutional factors within the context of sustainability, thereby bridging gaps between Dynamic Capabilities Theory and Institutional Theory. Practically, it suggests that firms should focus on green product innovation and develop GCC, while policymakers should foster trust and satisfaction through transparent and supportive policies to encourage green R&D investments.